Trial of celecoxib in amyotrophic lateral sclerosis - Cudkowicz, Merit E.; Shefner, Jeremy M.; Schoenfeld, David A.; Zhang, Hui; Andreasson, Katrin I.; Rothstein, Jeffrey D.; Drachman, Daniel B. (Annals of neurology, 2006)
Objective To determine whether chronic treatment with celecoxib, a cyclooxygenase‐2 inhibitor that has been shown to be beneficial in preclinical testing, is safe and effective in amyotrophic lateral sclerosis (ALS). Methods A double‐blind, placebo‐controlled, clinical trial was conducted. Three hundred research subjects with ALS were randomized (2:1) to receive celecoxib (800mg/day) or placebo for 12 months. The primary outcome measure was the rate of change in upper extremity motor function measured by the maximum voluntary isometric contraction strength. Secondary end points included safety, survival, change in cerebrospinal fluid prostaglandin E2 levels, and changes in the rate of decline of leg and grip strength, vital capacity, ALS Functional Rating Scale‐Revised, and motor unit number estimates. Results Celecoxib did not slow the decline in muscle strength, vital capacity, motor unit number estimates, ALS Functional Rating Scale‐Revised, or affect survival. Celecoxib was well tolerated and was not associated with an increased frequency of adverse events. Prostaglandin E2 levels in cerebrospinal fluid were not elevated at baseline and did not decline with treatment. Interpretation At the dosage studied, celecoxib did not have a beneficial effect on research subjects with ALS, and it was safe. A biological effect of celecoxib was not demonstrated in the cerebrospinal fluid. Further studies of celecoxib at a dosage of 800mg/day in ALS are not warranted. Ann Neurol 2006;60:22–31